Fraxinus caroliniana, Pop Ash - Michael G. Andreu; Melissa H. Friedman; Mary McKenzie; Heather V. Quintana; Robert J. Northrop (EDIS)
FOR 256, a 2-page fact sheet by Michael G. Andreu, Melissa H. Friedman, Mary McKenzie, Heather V. Quintana, and Robert Northrop, describes this native deciduous tree found in the wet soils of swamps, flatwoods, bottomlands, and riverbanks throughout the southeastern United States — scientific and common names, description, allergen, and applications. Includes references. Published by the UF School of Forest Resources and Conservation, June 2010.